# Wednesday November 20 Last time: $$ \ZZ \Lambda \iff \theset{ \lieh^* \to \ZZ_{\geq 0} \mid \sim } \\ e(\mu) \mapsto e_\mu \\ e(\lambda) e(\mu) = e(\lambda + \mu) \mapsto f \star g(\lambda) = \sum_{a+b=\lambda} f(a) g(b) $$ and $\mathrm{ch} L(\lambda) = \sum_{\mu \in \Lambda} \dim L(\lambda)_\mu e(\mu)$. We have the Kostant function $p(\lambda) = \# \theset{ (k_\alpha)_\alpha \mid -\lambda = \sum_{\alpha\in\Phi^+} k_\alpha \alpha }$ and the Weyl function $q = e_\rho \star \prod_{\alpha\in\Phi^+}(1 - e_{-\alpha}) = \prod_{\alpha\in\Phi^+} (e_{\alpha/2} - e_{-\alpha/2})$. **Lemma:** $p\star e_\lambda = \mathrm{ch} M(\lambda)$, so $q \star \mathrm{ch} M(\lambda) = e_{\lambda + \rho}$ and $q \star p = e_\rho$. ## Weyl's Character Formula (24.2-3) **Definition:** The *dot action* of $W$ is given by $w\cdot \lambda = w(\lambda + \rho) - \rho$, i.e. a reflection for hyperplanes passing through $-\rho$. E.g. for type $A2$, where $W(0) = 0$, we have: ![Type A2](figures/2019-11-20-09:19.png)\ And for the dot action, we have ![Image](figures/2019-11-20-09:22.png)\ where $W \cdot 0 = 0$ and $s(\alpha_1) = -\alpha_1$. **Theorem (Harish-Chandra):** If $L(\mu)$ is a composition factor of $M(\lambda)$, then $\mu \in W\cdot \lambda$ for $\mu \leq \lambda$. *Proof:* Postponed. > $\mathrm{ch}$ are characters, $L(\lambda)$ is a Verma module. *Remark:* If we sum over $\mu \leq \lambda$, we obtain \begin{align*} \mathrm{ch} M(\lambda) &= \sum_{\mu \in W \cdot \lambda} a_{\lambda \mu} \mathrm{ch} L(\mu) \\ \mathrm{ch} L(\lambda) &= \sum_{\mu \in W \cdot \lambda} b_{\lambda \mu} \mathrm{ch} M(\mu) \\ &= \sum_{W\cdot \lambda \in \Lambda} c_{\lambda W} \mathrm{ch} M(w\cdot \lambda) .\end{align*} **Theorem (Weyl's Character Formula):** If $\lambda \in \Lambda^+$, then $$ \mathrm{ch} L(\lambda) = \frac{ \sum_{w\in W} (-1)^{\ell(w)} e(w \cdot \lambda) }{ \sum_{w\in W} (-1)^{\ell(w)} e(w\cdot 0) } $$ *Proof*: We have $\mathrm{ch} L(\lambda) = \sum_{w} c_{\lambda w} \mathrm{ch} M(w\cdot \lambda)$, and so by the lemma, $$ q \ast \mathrm{ch} L(\lambda) = \sum c_{\lambda w} q \star \mathrm{ch} M(W(\lambda + \rho) - \rho) = \sum_w c_{\lambda w} e_{W(\lambda + p)} $$ Thus for all $\alpha \in \Phi^+$, we have $$ s_\alpha(q \star \mathrm{ch} L(\lambda)) = \sum_w c_{\lambda, s_\alpha w} e_{w(\lambda + \rho)} $$ On the other hand, by part (c) of the lemma, we have $$ (s_\alpha \star q) \star \mathrm{ch} L(\lambda) = -q \star \mathrm{ch} L(\lambda) = \sum_w -c_{\lambda, w} e_{w(\lambda+\rho)} $$ which implies that $c_{\lambda, s_\alpha w} = -c_{\lambda, w}$ by comparing term-by-term, and thus $c_{\lambda, w} = (-1)^{\ell(w)}$ because $c_{\lambda e} = 1$. In particular, $q = q \star e(0) = q \star \mathrm{ch} L(0) = \sum_{w\in W} (-1)^{\ell(w)} e_{w(\rho)}$, and thus \begin{align*} \mathrm{ch} L(\lambda) = \frac { \sum_w (-1)^{\ell(w)} e_{w(\lambda+p)} }{ \sum_w (-1)^{\ell(w)} e_{w(p)} } \\ = \frac { \sum_w (-1)^{\ell(w)} e(w\cdot \lambda) }{ \sum_w (-1)^{\ell(w)} e(w \cdot 0) }. \end{align*} $\qed$ *Example:* For type $A1$, we have $W = \Sigma_2 = \theset{\mathbf{1}, s}$. Take $\lambda = 3$ under \begin{align*} \Lambda \equiv \ZZ \\ \alpha_1 \to 2 \\ w_1 = \rho \to 1 ,\end{align*} from which we obtain \begin{align*} \mathrm{ch} L(3) = \frac { e(\mathbf{1} \cdot 3) - e(s\cdot 3) }{ e(\mathbf{1} \cdot 0) - e(s\cdot 0) } \\ = \frac{e(3) - e(-5)}{e(0) - e(-2)} \\ = e(3) + e(1) + e(-1) + e(-3) \quad\text{by long division} .\end{align*} **Corollary (Kostant's Dimension Formula):** If $\mu \leq \lambda \in \Lambda^+$, then $$ \dim L(\lambda)_\mu = \sum_{w\in W} (-1)^{\ell(w)} P(w\cdot \lambda - \mu). $$ *Proof:* $p\star e_\mu(w \cdot \lambda) = \sum_{a+b = w\cdot \lambda} p(a) e_\mu(h) = p(w\cdot \lambda - \mu)$, since this is the only term that survives. Then $p(w\cdot \lambda - \mu)$ is the coefficient for $e(\mu)$ in $\mathrm{ch} M(w\cdot \lambda) = \dim M(\lambda)_\mu$. Thus $\dim L(\lambda)_\mu = \sum_{w\in W} (-1)^{\ell(w)} \dim M(w\cdot \lambda)_\mu$. **Corollary (Weyl's Dimension Formula):** If $\lambda \in \Lambda^+$, then $$ \dim L(\lambda) = \frac{ \prod_{\alpha\in\Phi^+} (\lambda+\rho, \alpha\dual) }{ \prod_{\alpha\in\Phi^+} (\rho, \alpha\dual) } $$ *Proof (sketch)*: Define an operator $\del = \prod_{\alpha\in\Phi^+} \del_a$, where $\del_a: e(\mu) \mapsto (u, \alpha\dual) e(\mu)$. Then $\del$ is well-defined since $\del_\alpha \del_\beta = \del_\beta \del_\alpha$ for all $\alpha, \beta$, and (exercise) $\del$ is a derivation. Define an evaluation homomorphism $\nu: \sum_\mu c_\mu e(\mu) \mapsto \prod_\mu c_\mu$. Note that $\nu (\mathrm{ch} L(\lambda)) = \dim L(\lambda)$, and $\nu(q) = 0$ because $\nu(e_{\alpha_i - 1}) = 0$. *Claim:* $$ \nu( \del( q \star \mathrm{ch} L(\mu - \rho) ) ) = \abs{w} \prod_{\alpha\in\Phi^+} (\mu, \alpha\dual) $$ This is relatively straightforward once you know that you have a derivation and a homomorphism. With this claim, we have $$ \nu(\del(q \star \mathrm{ch} L(\lambda))) = \nu(\del q) \nu(\mathrm{ch} L(\lambda)) + \nu(q) \nu(\del \mathrm{ch} L(\lambda)) $$ where we can identify a number of terms, and then taking ratios yields Weyl's dimension formula.